Real exchange rate undervaluation and Indonesia's manufacturing exports - Rasbin; Mohamad Ikhsan; Beta Y. Gitaharies; Yoga Affandi (Cogent Economics & Finance, 2021)
This study analyzes the impact of real exchange rate undervaluation on Indonesia's manufacturing exports in 22 manufacturing industries throughout 1990-2015. The study was undertaken by modifying a partial equilibrium model of monopolistic competition for exporting firms and using the augmented mean group (AMG) method. This study confirms that the real exchange rate, both misalignment and changes in levels (depreciation/appreciation), are insignificant in affecting Indonesia's manufacturing exports. In addition, this study finds that manufactured exports are significantly determined by the manufactured exports in the previous period, real interest rates, real wages, labor productivity, and firm growth. This finding indicates that the exchange rate manipulation policy is not an important factor in strengthening the competitiveness of Indonesia's manufacturing exports. We suggest policies that play more important roles in driving manufacturing exports are creating a competitive and conducive business climate, lowering domestic interest rates, and reforming the labor system.
Keywords: C33; F10; F31; 330; augmented mean group; manufacturing exports; real exchange rate; undervaluation